Going out and the search for originality in China - Keane, Michael (Peking University Press, 2012)
Can China improve the competitiveness of its culture in world markets? Should it focus less on quantity and more on quality? How should Chinese cultural producers and distributors target audiences overseas? These are important questions facing policy makers today. In this paper I investigate how China might best deploy its soft power capabilities: for instance, should it try to demonstrate that it is a creative, innovative nation, capable of original ideas? Or should it put the emphasis on validating its credentials as an enduring culture and civilisation? In order to investigate these questions I introduce the cultural innovation timeline, a model that explains how China is adding value. There are six stages in the timeline but I will focus in particular on how the timeline facilitates cultural trade. In the second part of the paper I look at some of the challenges facing China, particularly the reception of its cultural products in international markets.